Comparison the level of parathyroid gland hormone and body mass index normal in Iraqi population in age between (4-20) year with their reference values - ABD AL-HUSSEIN, SAFFANA MAEN (Journal of medical and pharmaceutical sciences, 2019)
This study aimed to compare between PTH level and BMI in female and male separately then the results were compared between female and male. The aim of this study is to know the cause of differences in hormone elevation and weight in female compared with male for the same age (4 – 20) year old in Iraqi society and the effect of stress, physiological change on these results. A descriptive approach has been used in this study to research analysis, two variables were used: PTH, BMI. The conclusion of this study is that: there is an elevation in female serum PTH level with elevation in their weights in ages (4 – 9), (10 -14), (15 – 20) year, when these results compared with the results from male in the same age it’s clear that they were higher, so; the handling of this issue by interesting in sport in ordinary life and in school and consideredit an important lesson Based on direction of education ministry.